COMPARATIVE PROTEOMIC ANALYSIS IN MICRODISSECTED RENAL VESSELS OF HYPERTENSIVE AND NORMOTENSIVE RATS. (June 2018) - Vlahakos, D.; Barkas, G.; Makridakis, M.; Zoidakis, J.; Vlahou, A.; Charonis, A.
Abstract : Objective: Systemic hypertension has a profound impact on the renal vascular physiology and functionality. Our goal was to identify the biological pathways and macromolecules of the renal arteriolar wall, which are involved with the development of hypertrension. Design and method: Tissue derived exclusively from renal vessels of 4 Spontaneously Hypertensive Rat (SHR) and 4 normotensive controls (Wistar Kyoto, WKY) at 20 weeks using Laser Capture Microdissection on 14 micrometer cryosections was used. High sensitivity proteomic analysis was performed in the microdissected homogenized material in order to detect early molecular alterations associated with hypertension of the renal vessels before the onset of vascular damage. Results: Proteomic analysis revealed 688 proteins; 550 proteins were found in both groups, of which 58 proteins were differentially expressed (15 proteins were up-regulated and 43 proteins were down-regulated in SHR). 71 proteins were found exclusively in control WKY rats and 67 exclusively in SHR rats. Pathway enrichment analysis revealed 114 and 111 pathways in WKY and SHR, respectively and 106 common pathways in both groups. Many of the interesting differentially expressed proteins identified in our study are relevant to vascular tone regulation. Thus proteins involved with NO and vasodilation and affecting eNOS include Xaa-Pro aminopeptidase 1 (XPP1), N (G) N (G)-dimethylarginine dimethylaminohydrolase 1 (DDAH1), Dehydropteridine reductase (DHPR), whereas proteins involved with blood pressure regulation by the renin-angiotensin system include Glutamyl aminopeptidase / Aminopeptidase A (AMPE) and Aminopeptidase N (AMPN). Moreover, pathway enrichment analysis revealed that the eNOS activation pathway is disregulated only in the hypertensive SHR animals. Conclusions: Our study demonstrates that hypertension causes early proteomic changes in the renal vessels of SHR compared to WKY. These changes are relevant to vascular tone regulation and consequently may be involved in the development of vascular damage and hypertensive nephrosclerosis. Further studies are required to explore whether these pathways and molecules are involved with hypertensive nephrosclerosis and to identify components that could be considered new therapeutic targets